Heterodimerization of Lrrk1-Lrrk2: Implications for LRRK2-associated Parkinson disease - Dachsel, Justus C. (2010)
LRRK2 mutations are recognized as the most frequent genetic cause of both familial and sporadic parkinsonism identified to date. A remarkable feature of this form of parkinsonism is the variable penetrance of symptom manifestation resulting in a wide range of age-at-onset in patients. Herein we use a functional approach to identify the Lrrk1 protein as a potential disease modifier demonstrating an interaction and heterodimer formation with Lrrk2. In addition, evaluation of LRRK1 variants in our large Lrrk2 p.G2019S-parkinsonism series from a Tunisian (n=145) identified a missense mutation (p.L416M) resulting in an average 6.2 years younger age at disease onset. In conclusion we show for the first time that the interaction of Lrrk1-Lrrk2 can form protein dimers and this interaction may influence the age of symptomatic manifestation in Lrrk2-parkinsonism patients.